Experimental and numerical investigation on assessing local bearing behavior of a pultruded GFRP bridge deck. (15th November 2018) - Xin, Haohui; Mosallam, Ayman S.; Liu, Yuqing; Wang, Congzhe; He, Jun
Abstract: In this study, a methodology proposing size reduction of flat steel bearing plates that are commonly used in experimentally evaluating composite deck to transfer and distribute simulated vehicles loads to the top of bridge deck specimens is presented. The proposed methodology considers the tire-to-deck effects based on both a contact pressure distribution model and finite element (FE) simulation results. Ultimate capacity and associated failure modes for the following two loading cases: (i) moment-dominated, and (ii) moment-shear coupled loads were experimentally evaluated. Experimental results showed that the ultimate capacity for moment-dominated loading case is 35.60 kN, while capacity for the same composite deck when subjected to a moment-shear coupled load is 44.34 kN. Experimental results indicated that the initiation of failure for both loading cases was in the form of the development of longitudinal cracks at both top flanges and at outer web section near the loading side. Finite element models that consider lamina damage were developed and analyzed. A good agreement between numerical and experimental results is achieved.